Método da eletrorresistividade aplicado à identificação de derivados de hidrocarbonetos em aquífero livre - Freitas, Mariana Duarte Nogueira [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The contamination of groundwater is a subject of great importance, since a lot of people use this kind of source for public supply. Due to the rapidity and low cost in environmental studies, geophysical methods have been an alternative in the analysis of contaminated areas. In this way, the work presented here aims at the detection and monitoring of contamination from hydrocarbon derivatives in the area of the Alberto Pasqualini Refinery, located in Canoas/RS, from the geophysical method of Eletroresistivity - Vertical Electrical Sounding Technique (VES). From this technique it was possible to observe values of depth of water level, resistivity and longitudinal conductance, through which it was possible to make the potentiometric map of the area, in order to understand the flow of water and consequently of the contaminants in the region, besides the estimation of the degree of protection of the free aquifer, from correlations of these parameters. Finally, potential sites of contamination of the aquifer were also estimated, and it was found that the vast majority of the region may be contaminated

A contaminação das águas subterrâneas é um assunto de grande importância, devido ao fato de muitas pessoas utilizarem essa fonte para abastecimento público. Devido à rapidez e o baixo custo em estudos ambientais, os métodos geofísicos tem sido uma alternativa na análise de áreas contaminadas. Desta forma, o trabalho aqui apresentado visa à detecção e monitoramento de contaminações provenientes de derivados de hidrocarbonetos na área da Refinaria Alberto Pasqualini, localizada em Canoas/RS, a partir do método geofísico de Eletrorresistividade - Técnica de Sondagem Elétrica Vertical (SEV). A partir dessa técnica foi possível observar valores de profundidade do nível d'água, resistividade e condutância longitudinal, por meio dos quais foi possível a confecção do mapa potenciométrico da área, a fim de entender-se o fluxo das águas e consequentemente dos contaminantes na região, além da estimativa do grau de proteção do aquífero livre, a partir de correlações desses parâmetros. Por fim também foram estimados potenciais sítios de contaminação do aquífero, e constatouse que a grande maioria de região pode estar contaminada
Keywords: Águas subterrâneas; Hidrocarbonetos; Aquiferos; Hidrogeologia; Água - Poluição; Geofisica; Rio Grande do Sul